Activity of an A-L-Rhamnosidase Produced by Aspergillus niger During Solid State Fermentation of Coffee Pulp Wastes - Kahar Muzakhar; Rudju Winarsa (UIN Sunan Gunung Djati Bandung, 2019)
An α-L-Rhamnosidase released by Aspergillus niger during solid-state fermentation (SSF) using coffee pulp (CP) wastes media has been investigated. The activity of α-L-Rhamnosidase based on reducing sugar production against 2% CP alkali extract substrate in 50 mM acetate buffer pH 5. The maximum activity of α-L-Rham-nosidase was obtained in sixth-day SSF with reducing sugar pro-duction of 13 μg/mL. The enzyme is actively hydrolyzed 0.1% p-ni-trophenyl-α-L-rhamnopyranoside (PNP-Rha) to 95% from initial concentration. Purification using DEAE-Toyopearl 650M increased hydrolysis activity ten times against the substrate, reaching 134 μg/mL of reducing sugar. Optimum enzyme activity at pH 4.5 and 50°C, while stable at pH and temperature in a pH range of 3.5-7 and below 50°C.